(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Background: Cranial index & cranial dimensions are invaluable tools in craniometrical studies for determining racial & sexual dimorphism. It is useful tool in Forensic Medicine, anthropology & genetic studies. Aims & Objectives: In present study, attempt has been made to find out Cephalic Index (CI) in males & females of Chhattisgarh. Material and Method: This study was carried out on 310 males & females of Chhattisgarh in age group of 18-25 years. Cranial length and breadth was taken & Cephalic Index calculated. Results: Mean value for cephalic index is 78.25 for males and 72.10 for females. Conclusion: Majority of the population in this study group is mesocephalic.